Graphene Oxide Incorporated Forward Osmosis Membranes With Enhanced Desalination Performance and Chlorine Resistance - Li, Zhanguo; Wang, Yi; Han, Mengwei; Wang, Dayong; Han, Shitong; Liu, Zequn; Zhou, Ningyu; Shang, Ran; Xie, Chaoxin (Frontiers in Chemistry, 2020)
In this work, grapheme oxide (GO) nano-sheets were synthesized and dispersed in the aqueous phase for the interfacial polymerization (IP) process to develop a new type of thin-film composite (TFC) membranes for forward osmosis (FO) applications. The effects of the GO concentrations on the membrane surface and cross-sectional morphologies and FO desalination performances of the as-prepared TFC membranes were investigated systematically. Compared with the control membrane, the optimal GO-incorporated TFC membrane displayed higher water flux, lower specific reverse solute flux (SRSF) and structure parameter. Moreover, the optimized membrane showed 75.0 times higher chlorine resistance than the control membrane. In general, these new type of membranes could be an effective strategy to synthesize high-performance FO membranes with good desalination performance and chlorine resistance.